The Analysis Of Relationship Between Students Academic Procrastination Behavior And Students Learning Motivation - Abidin, Dindin; AK Sembiring, Desy; Nofirman; Setiawan , Asep; Rino Vanchapo , Antonius (Mudir : Jurnal Manajemen Pendidikan, 2023)
Motivation to learn has an important role in arousing students' enthusiasm and initiative to learn. Students have a busy time, and a lack of initiative leads to delaying learning behavior, so that the existence of learning motivation can reduce the occurrence of academic procrastination behavior. The purpose of this study is to ascertain the connection between students' academic procrastinating behavior and learning motivation. The correlational approach is employed in this investigation. A total of 300 students were included in the sampling, which was done using a purposive sampling technique. A learning motivation questionnaire, an academic procrastination questionnaire, and an interview guide sheet were the tools employed. Utilizing the product moment correlation method, data collection was evaluated. The findings revealed a correlation coefficient (rxy) of -0.659 with a significance level of 0.000, indicating a significant negative relationship between students' academic procrastination behavior and their learning motivation. This indicates that the two variables have a strong relationship with the category.